Neuroprotective effects of testosterone on ischemia/reperfusion injury of the rabbit spinal cord. Issue 2 (February 2015) - Gürer, Bora; Kertmen, Hayri; Kasim, Emin; Yilmaz, Erdal Resit; Kanat, Burhan Hakan; Sargon, Mustafa Fevzi; Arikok, Ata Türker; Ergüder, Berrin Imge; Sekerci, Zeki
Abstract: Aim: Previous studies demonstrated the neuroprotective effects of testosterone, but no previous study has examined the neuroprotective effects of testosterone on spinal cord ischemia/reperfusion injury. The purpose of this study was to evaluate whether testosterone could protect the spinal cord from ischemia/reperfusion injury. Methods: Rabbits were randomised into four groups of eight animals as follows: group 1 (control), group 2 (ischemia), group 3 (methylprednisolone) and group 4 (testosterone). In the control group only a laparotomy was performed. In all other groups, the spinal cord ischemia model was created by the occlusion of the aorta just caudal to the renal artery. Levels of malondialdehyde and catalase were analysed, as were the activities of caspase-3, myeloperoxidase, and xanthine oxidase. Histopathological and ultrastructural evaluations were performed. Neurological evaluation was performed with the Tarlov scoring system. Results: After ischemia-reperfusion injury, increases were found in caspase-3 activity, myeloperoxidase activity, malondialdehyde levels, and xanthine oxidase activity. In contrast, decreases in catalase levels were observed. After the administration of testosterone, decreases were observed in caspase-3 activity, myeloperoxidase activity, malondialdehyde levels, and xanthine oxidase activity, whereas catalase levels increased. Furthermore, testosterone treatment showed improved results concerning histopathological scores, ultrastructural score and Tarlov scores. Conclusions: Our results revealed for the first time that testosterone exhibits meaningful neuroprotective activity following ischemia-reperfusion injury of the spinal cord.